Autoimmune Progressive Fibrosing Interstitial Lung Disease: Predictors of Fast Decline - Alexandra Nagy; Tamas Nagy; Abigel Margit Kolonics-Farkas; Noemi Eszes; Krisztina Vincze; Eniko Barczi; Adam Domonkos Tarnoki; David Laszlo Tarnoki; György Nagy; György Nagy; Emese Kiss; Emese Kiss; et al. (Frontiers Media S.A., 2021)
A subset of interstitial lung diseases (ILDs) with autoimmune traits-including connective tissue disease-associated ILD (CTD-ILD) and interstitial pneumonia with autoimmune features (IPAF)-develops progressive fibrosing (PF)-ILD. The aim of our study was to evaluate the clinical characteristics and predictors of longitudinal lung function (LF) changes in autoimmune PF-ILD patients in a real-world setting. All ILD cases with confirmed or suspected autoimmunity discussed by a multidisciplinary team (MDT) between January 2017 and June 2019 (n = 511) were reviewed, including 63 CTD-ILD and 44 IPAF patients. Detailed medical history, LF test, diffusing capacity of the lung for carbon monoxide (DLCO), 6-min walk test (6MWT), blood gas analysis (BGA), and high-resolution computer tomography (HRCT) were performed. Longitudinal follow-up for functional parameters was at least 2 years. Women were overrepresented (70.1%), and the age of the IPAF group was significantly higher as compared to the CTD-ILD group (p < 0.001). Dyspnea, crackles, and weight loss were significantly more common in the IPAF group as compared to the CTD-ILD group (84.1% vs. 58.7%, p = 0.006; 72.7% vs. 49.2%, p = 0.017; 29.6% vs. 4.8%, p = 0.001). Forced vital capacity (FVC) yearly decline was more pronounced in IPAF (53.1 ± 0.3 vs. 16.7 ± 0.2 ml; p = 0.294), while the majority of patients (IPAF: 68% and CTD-ILD 82%) did not deteriorate. Factors influencing progression included malignancy as a comorbidity, anti-SS-A antibodies, and post-exercise pulse increase at 6MWT. Antifibrotic therapy was administered significantly more often in IPAF as compared to CTD-ILD patients (n = 13, 29.5% vs. n = 5, 7.9%; p = 0.007), and importantly, this treatment reduced lung function decline when compared to non-treated patients. Majority of patients improved or were stable regarding lung function, and autoimmune-associated PF-ILD was more common in patients having IPAF. Functional decline predictors were anti-SS-A antibodies and marked post-exercise pulse increase at 6MWT. Antifibrotic treatments reduced progression in progressive fibrosing CTD-ILD and IPAF, emphasizing the need for guidelines including optimal treatment start and combination therapies in this special patient group.